The Effectiveness of Turnsheet Media in Increasing Mother's Knowledge about Early Detection of Certificate Cancer in the Work Area of Puskesmas Jayakerta - Dwi Hustiati; Rahayu Khairiah (Asian Journal of Community Services, 2023)
Health is something that is important for humans, without health humans cannot carry out their daily activities. The state of health according to the World Health Organization (WHO) is a state of well-being including physical, mental and social that is free from disease or disability. Health is an important factor for improving the quality of human life socially and economically. to find out the factors that know the relationship between the level of knowledge of the Acetic Acid Visual Inspection test with the participation of women in carrying out the examination. Analytical with cross-sectional approach. The sample in this study was 30 respondents at the Jayakerta Health Center in November 2022. The results of this study indicate that there is an influence of flipchart media on increasing mother's knowledge about early detection of cervical cancer (p value = 0.014). The puskesmas is expected to provide more information in the puskesmas or posyandu environment such as posters, leaflets, banners related to the increasing importance of mother's knowledge about early detection of cervical cancer.